(untitled) (Research, Society and Development, 2025)
The objective was to review and map the existing literature on glycemic control in diabetic patients undergoing preoperative fasting, identify the associated risk factors, considering management and control strategies for possible complications, and provide an overview of the available evidence. Methodology: This is an integrative literature review, using the PICO strategy to search for scientific articles, integrative reviews, meta-analyses, guidelines, and clinical protocols. The study focuses on adults and elderly patients with Diabetes Mellitus undergoing surgical interventions. Including current studies within the period of 5 years, from 2019 to 2024. Studies involving pediatric patients, non-diabetic patients, non-surgical procedures, and studies that do not evaluate glycemic control during fasting will be excluded from the review. Results: The review covered 16 main studies, and the other complementary references allowed for a broad analysis of glycemic control in diabetic patients undergoing preoperative fasting. The findings showed that careful perioperative glycemic monitoring and control significantly reduce the risk of complications, including surgical site infections, delayed healing, hemodynamic instability, insulin resistance consequently leading to hyperglycemia and hypoglycemia. Conclusion: The implementation of glycemic control strategies not only reduces the risks associated with surgical procedures but also improves the quality of life of diabetic patients, promoting a faster and safer recovery.